2009
DOI: 10.1186/1756-9966-28-104
|View full text |Cite
|
Sign up to set email alerts
|

Statistically significant association of the single nucleotide polymorphism (SNP) rs13181 (ERCC2) with predisposition to Squamous Cell Carcinomas of the Head and Neck (SCCHN) and Breast cancer in the north Indian population

Abstract: Background: Non-synonymous single nucleotide polymorphisms (SNPs) within vital DNA repair genes may cause reduction of activity leaving the genome unrepaired resulting in genomic instability and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…However, it was consistent with data reported by Zhai et al [54] in Chinese people. In contrast, Vineis P et al [5], Zhang J et al [55], Spitz MR et al [56] and Mitra AK et al [57] reported that ERCC2 rs13181 and rs1799793 minor alleles are risk factors to cancer development and associated with low DNA repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was consistent with data reported by Zhai et al [54] in Chinese people. In contrast, Vineis P et al [5], Zhang J et al [55], Spitz MR et al [56] and Mitra AK et al [57] reported that ERCC2 rs13181 and rs1799793 minor alleles are risk factors to cancer development and associated with low DNA repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Sturgis et al (2000) reported that 13181CC was associated with a borderline increased risk (adjusted OR = 1.55; 95%CI = 0.96-2.52) of SCCHN and it was higher in older subjects (OR = 2.22; 95%CI = 1.03-4.80) and current drinkers (OR = 2.59; 95%CI = 1.25-5.34). Mitra et al (2009) found statistically significant increased SCCHN risk in individuals with the variant genotypes of rs13181: (OR = 1.680, 95%CI 1.014 to 2.784), (OR = 1.531, 95%CI 1.092 to 2.149) and (OR = 1.560, 95%CI 1.128 to 2.158). The others came to a different conclusion.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 15 eligible case-control studies on the association between XPD Lys751Gln polymorphism and HNC risk were included for this meta-analysis (Sturgis et al, 2000;Rydzanicz et al, 2005;Huang et al, 2005;Kietthubthew et al, 2006;Matullo et al, 2006;Ramachandran et al, 2006;Bau et al, 2007;Majumder et al, 2007;Harth et al, 2008;Abbasi et al, 2009;Mitra et al, 2009;Jelonek et al, 2010;Ji et al, 2010;Sliwinski et al, 2011). Table 1 presents the main characteristics of these studies.…”
Section: Study Characteristicmentioning
confidence: 99%
“…ERCC2 (XPD) encodes a protein component of the TFIIH subunit which denatures the double helix of DNA in preparation for excision of bulky DNA adducts (6, 67). Over 20 previous case-control studies have studied rs13181 and HNC risk, with the majority finding null associations (8-12, 15, 17, 18, 20-23, 25, 26, 30, 31, 33-35, 37, 38, 45, 48). The largest study, based on data from the International Head and Neck Cancer Epidemiology Consortium, found no association between rs13181 and HNC risk (Gln/Gln vs. Lys/Lys, OR=1.03, 95% CI=0.88, 1.21) (15).…”
Section: Discussionmentioning
confidence: 99%